Characteristics of Communication through Online Social Networks in Central Public Institutions in Romania - Strempel, Christian-Gabriel; Briciu, Victor-Alexandru (Association of Economists and Managers of the Balkans, 2024)
This paper examines how central public institutions in Romania use social media to communicate with citizens. The study investigates how these institutions use Facebook to engage with their target audiences and what factors influence the number of followers they have. The research methodology involves examining the activity of the Facebook pages of these institutions. The findings reveal significant differences in fan engagement across different pages. Moreover, post types and frequency do not have a high impact on page growth compared to the number of shares. The results highlight that although there is a communication plan in place by the central public administration in Romania, there is no uniform communication across the ministries.